Standardizing an Experimental Murine Model of Extraparenchymal Neurocysticercosis That Immunologically Resembles Human Infection - Espinosa-Cerón, Alejandro; Méndez, Alejandro; Hernández-Aceves, Juan; Juárez-González, Juan C.; Villalobos, Nelly; Hernández, Marisela; Díaz, Georgina; Soto, Paola; Concha, Luis; Pérez-Osorio, Iván N.; Ortiz-Retana, Juan J.; Bobes, Raúl J.; et al. (MDPI, 2023)
Background: Neurocysticercosis (NCC) is endemic in non-developed regions of the world. Two forms of NCC have been described, for which neurological morbidity depends on the location of the lesion, which can be either within the cerebral parenchyma or in extraparenchymal spaces. The extraparenchymal form (EXP-NCC) is considered the most severe form of NCC. EXP-NCC often requires several cycles of cysticidal treatment and the concomitant use of glucocorticoids to prevent increased inflammation, which could lead to intracranial hypertension and, in rare cases, to death. Thus, the improvement of EXP-NCC treatment is greatly needed. Methods: An experimental murine model of EXP-NCC, as an adequate model to evaluate new therapeutic approaches, and the parameters that support it are described. EXP-NCC was established by injecting 30 Taenia crassiceps cysticerci, which are less than 0.5 mm in diameter, into the cisterna magna of male and female Wistar rats. Results: Cyst implantation and infection progression were monitored by detecting the HP10 antigen and anti-cysticercal antibodies in the serum and cerebral spinal fluid (CSF) of infected rats and by magnetic resonance imaging. Higher HP10 levels were observed in CSF than in the sera, as in the case of human EXP-NCC. Low cell recruitment levels were observed surrounding established cysticerci in histological analysis, with a modest increase in GFAP and Iba1 expression in the parenchyma of female animals. Low cellularity in CSF and low levels of C-reactive protein are consistent with a weak inflammatory response to this infection. After 150 days of infection, EXP-NCC is accompanied by reduced levels of mononuclear cell proliferation, resembling the human disease. EXP-NCC does not affect the behavior or general status of the rats. Conclusions: This model will allow the evaluation of new approaches to control neuroinflammation and immunomodulatory treatments to restore and improve the specific anti-cysticercal immunity in EXP-NCC.
Keywords: experimental model; neurocysticercosis; neuroinflammation; T. crassiceps